TANGGUNG JAWAB PENDIDIKAN PADA ANAK DALAM PERSPEKTIF ISLAM - Sulaiman, Muhammad; Abidin, Achmad Anwar (Atthiflah: Journal of Early Childhood Islamic Education, 2024)
Education is a fundamental right for human beings, especially for children. If ignored, there will be chaos in all aspects of life because of ignorance. In this article discussed the responsibility of education on the child, such responsibility is "photographed" from the point of view of Islam. This responsibility, if fulfilled, must be clearly grounded and must be firmly supported pillars. Getting an Islamic education is the right and obligation of all Muslims. The foundation is the Islamic Aqidah and the first organizer is the family i.e. the parents, the main organizer is the government which is operationally carried out by the school. Competent teachers with Islamic personality must be in it. The community is a supporting organizer, so that the burden on the government is lighter and education services are more evenly distributed. Family, school, community and government work in synergy. Helping each other, strengthening and competing in advancing education. So that the goal of Islamic education can be realized, which is to produce people of faith, piety and mastery of science and technology. In other words, producing people with character, namely good people, people with good hearts, good thoughts and good deeds